Linking the cell cycle to histone modifications: Dot1, G1/S, and cycling K79me2. - Mellor, J (2009)
In a recent issue of Molecular Cell, Schulze et al. (2009) described distinct distributions and regulation of Dot1-dependent methylation states at lysine 79 on histone H3 and showed cell-cycle regulation of K79 dimethylation on genes expressed during the G1/S phase.